1994
DOI: 10.1136/gut.35.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peptic ulcer in Helicobacter pylori positive blood donors.

Abstract: This study aimed to determine the importance of raised antibodies to Helicobacter pylon in an asymptomatic population. A total of 128 asymptomatic blood donors who were seropositive for H pylon and consented to endoscopy were investigated. These subjects were from a population of 1010 blood donors screened for antibodies to H pylori. A questionnaire was completed to determine if any subjects had complained of symptoms, and they subsequently had endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 16 publications
(1 reference statement)
4
38
1
Order By: Relevance
“…Other studies conducted among blood donors in developed countries have usually not revealed a decline in H. pylori seroprevalence similar to the one observed by us (5,7,15,20,26,(33)(34)(35)(36). A closer inspection of the previous data, however, unveils lower-than-expected seroprevalence rates above the age of 50 in several studies, (5,34,36), but few of them included subjects who were older than 60.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Other studies conducted among blood donors in developed countries have usually not revealed a decline in H. pylori seroprevalence similar to the one observed by us (5,7,15,20,26,(33)(34)(35)(36). A closer inspection of the previous data, however, unveils lower-than-expected seroprevalence rates above the age of 50 in several studies, (5,34,36), but few of them included subjects who were older than 60.…”
Section: Discussionsupporting
confidence: 69%
“…In European epidemiological studies, blood donors are often used to represent the general population since all European countries have unpaid donors (34,36). The appropriateness of this assumption has not been rigorously tested for H. pylori seroprevalence.…”
mentioning
confidence: 99%
“…The difference between the two studies rested on a comparison of asymptomatic subjects (healthy volunteers) and PU patients (3), while the present findings were based on a controlled study with consecutive patients with dyspeptic symptoms (patients with NUD and patients with PU). However, in another study with asymptomatic subjects, Vaira et al (21) showed that of 128 of 1,010 asymptomatic blood donors who were seropositive and who had consented to endoscopy, 121 had chronic active gastritis. Among these 121 patients, 25 had PU, 21 had erosive duodenitis, and 2 had gastric cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The availability of commercial kits using puri®ed antigens represents a real advancement in terms of sensitivity and speci®city. 2 H. pylori infection is mostly asymptomatic 2,3 because the organism tends to have a symbiotic relationship with the host. However, patients with dyspeptic symptoms are very often infected with H. pylori although it is SUMMARY Aim: To assess the seroprevalence of Helicobacter pylori infection in a large series of patients with upper gastrointestinal symptoms referred for their ®rst upper gastrointestinal endoscopy, and to evaluate any association with disease.…”
Section: Introductionmentioning
confidence: 99%